STRATEGI HUMAS PEMKOT BONTANG DALAM PENYEBARLUASAN INFORMASI PEMBANGUNAN DAERAH DI KELURAHAN GUNTUNG KOTA BONTANG - Anna Kus Saparti; Adam Idris; Muhammad Jamal Amin (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This study aimed to identify and analyze the strategies used by the PR of Bontang City Government in disseminating information on regional development in Guntung Subdistrict. This research uses descriptive qualitative research methods, the data collections were done through interviews and documentation. Based on the research that has been done, it can be stated that the strategy of Bontang City Government PR in the dissemination of regional development information in Guntung is done through printed media which are newspapers, magazines, bulletins, banners, balihos, and leaflets; electronic media which are telelevision and radio broadcasts, and face to face communication media which is interactive dialogues between the city government and the community members.